Neurogenic component of different models of acute inflammation in the rat knee joint. Issue 11 (November 1991) - Lam, F Y; Ferrell, W R
Abstract : This study was performed to investigate whether different models of acute joint inflammation showed a neurogenic component and to establish whether this is mediated through sensory afferent or sympathetic efferent nerve fibres. Intra-articular injection of 2% carrageenan, 20 micrograms substance P, 1% formalin, and 2% urate all produced an inflammatory response. Prior surgical denervation of the joint significantly inhibited this response in the carrageenan and formalin models, but not the others. Pretreatment of the joint with 1% capsaicin (about one week previously) significantly reduced the inflammatory response in all models except formalin. In animals pretreated long term with reserpine (to deplete sympathetic nerve endings of their neurotransmitters) significant reductions occurred in the inflammatory responses to substance P and urate. Intraarticular injection of compound 48/80 produced a marked inflammatory response, which was only significantly reduced by capsaicin pretreatment. These results suggest that both the formalin and carrageenan models of inflammation depend to some extent on the integrity of the sensory innervation of the joint, and thus have a neurogenically mediated component to the inflammatory process they generate. In these models there seems to be little contribution from sympathetic efferent fibres. Each model of inflammation showed a different pattern of response to the pretreatments, suggesting that the mediators of the inflammatory process may differ in each case.